High Prevalence of Mycoplasma penetrans in Chlamydia trachomatis Positive Rectal Samples From Men: A Brief Report - Pérez-Prieto, Inmaculada; Skafte-Holm, Axel; Jensen, Jørgen Skov (Frontiers in Microbiology, 2022)
Mycoplasma penetrans has gained increased attention in relation to sexually transmitted infections, however, its pathogenic potential and prevalence in different populations remains to be elucidated. Among 293 Chlamydia trachomatis positive rectal samples submitted for lymphogranuloma venereum typing, M. penetrans was detected by PCR in 13.4% of 231 male samples.